The Distribution of Cobalt between Alloy, Matte and Iron Silicate Slag at 1573 K - Liu, X.; Grimsey, Eric (AusIMM, 1994)
The distribution of cobalt between Co-Au-Fe alloy, Co-Fe-Au-S matte and alumina-saturated iron silicate slag has been measured at 1573 K, with the sulphur and oxygen pressures controlled by SO2, CO2 and CO gas mixtures. The use of an alloy in contact with matte provided a novel method for directly evaluating the activity of cobalt in the presence of sulphur, allowing the activities of cobalt oxide and cobalt sulphide to be calculated. Cobalt solubility in slag was assessed thermodynamically in terms of these activities and the data compared with those for sulphur-free slags. Although it has been accepted generally that cobalt dissolves in slag only as oxide, this work presents evidence for the dissolution of cobalt as sulphide in addition to oxide.